Modeling and optimization of inter-plant indirect heat exchanger networks by a difference evolutionary algorithm - Tian, Yitong; Jin, Yuhui; Li, Shaojun (Chemical engineering science, 2020)
•A simultaneous multi-plant indirect heat exchanger network model was proposed.•Using DE to search for the temperatures of the two ends in the intermediate fluids circuit.•Deterministic method and heuristic algorithm were combined.•Connection cost and pump related cost were involved. Inter-plant indirect heat integration via intermediate fluid circuit is an efficient energy-saving and heat recovery method, but traditional optimization methods, such as sequential synthesis, may not provide the best solutions. This paper addresses a multi-plant indirect heat exchanger network problem using a two-layer simultaneous synthesis method. To reduce the nonlinear constraints in the simultaneous heat exchanger network model, the outer layer uses a differential evolution algorithm to determine the temperatures of the intermediate fluid, while the inner layer uses a deterministic method to obtain the heat capacity flow rate of the intermediate fluid and the heat exchanger network configuration. Optimization was performed to minimize the total annualized cost, as the sum of utility cost, heat exchanger cost, pump cost, and pipe cost. The differential evolution algorithm in the outer layer improved the simultaneous synthesis efficiency in the inner MINLP model and also provided better results in the case studies.